Design of 7-level cascade asymmetric multilevel inverter for renewable energy applications using FPGA - Afarulrazi Abu Bakar; Hazwaj Mhd Poad; Benjamin Ho Hao Xian; Tharnisha Sithananthan; Wahyu Mulyo Utomo; Triyanto Pangaribowo (Institute of Advanced Engineering and Science, 2026)
The increasing focus on renewable energy has driven the need for efficient and reliable power converters. Multilevel inverters offer low harmonic distortion and high-quality output but often suffer from design complexity and excessive component count. This study presents the design and implementation of a 7-level cascaded asymmetric multilevel inverter optimized for renewable energy applications. The proposed topology utilizes a cascade structure with asymmetric DC voltage sources to generate seven voltage levels, providing a practical balance between performance and simplicity. The design was first validated through MATLAB/Simulink software to analyze circuit operation and evaluate the total harmonic distortion (THD) performance. Experimental evaluation was then conducted using a hardware prototype to verify simulation results. Without a filter, the THD from the simulation was 21.31%, while the experimental setup recorded a slightly higher value of 21.61%, indicating a marginal difference of 0.21%. With a filter, the simulation achieved a THD of 3.81%, whereas the experimental setup outperformed with a THD of 1.5%, showing a notable reduction of 2.31%. These findings confirm the proposed inverter’s capability to deliver superior power quality and operational efficiency. The combination of simulation and experimental validation demonstrates the practicality and reliability of the 7-level cascade asymmetric multilevel inverter for renewable energy applications.